Systematic review of injuries in the men`s and women`s National Basketball Association - Lian, J.; Sewani, F.; Dayan, I.; Voleti, P. B.; Gonzalez, D.; Levy, I. M.; Musahl, V.; Allen, A. (The American Journal of Sports Medicine, 2022)
Background: Numerous studies have reported the incidence and outcomes of injuries in the men`s and women`s National Basketball Association (NBA and WNBA, respectively).